Bolivia : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This Informational Annex highlights the ongoing Country Partnership Strategy (CPS) for the fiscal period 2012-15, which is guiding World Bank support to Bolivia. The CPS consists of a program of lending operations and knowledge activities along four pillars: (1) sustainable productive development; (2) climate change and disaster risk management; (3) human development and access to basic services; and (4) public sector effectiveness. In addition, the strategy incorporates gender, governance, and anticorruption as cross-cutting themes. These areas respond to government requests and priorities outlined in the National Development Plan, while also making the most of the World Bank's comparative advantage. For the remainder of the CPS period, efforts will involve more programmatic interventions, new instruments, and more innovative approaches and will now include financing from the International Bank for Reconstruction and Development.